2021
DOI: 10.3390/jzbg2020010
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 on Animals in Zoos: A Longitudinal Multi-Species Analysis

Abstract: Prolonged and repetitive COVID-19 facility closures have led to an abrupt cessation of visitors within UK and Irish zoos for variable periods since March 2020. This study sought to increase understanding of the impact of closures and reopenings on animal behaviour, thereby broadening understanding of whether zoo animals habituate to visitors. Data were collected from June to August 2020 at two UK facilities on eight species (n = 1 Chinese goral, n = 2 Grevy’s zebra, n = 11 swamp wallaby, n = 2 Rothschild’s gir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 25 publications
6
37
0
Order By: Relevance
“…The increase in amphibian visibility in the Golden Mantella Exhibit in September, compared to August (Figure 1), may indicate a short habituation period to visitor presence, and such periods of habituation have also been noted in other studies [21]. Combined with the trend seen in March (Figure 1), golden mantella may recover quicker to new situations.…”
Section: Ecological and Evolutionary Explanations For An Amphibian Visitor Effectsupporting
confidence: 73%
See 1 more Smart Citation
“…The increase in amphibian visibility in the Golden Mantella Exhibit in September, compared to August (Figure 1), may indicate a short habituation period to visitor presence, and such periods of habituation have also been noted in other studies [21]. Combined with the trend seen in March (Figure 1), golden mantella may recover quicker to new situations.…”
Section: Ecological and Evolutionary Explanations For An Amphibian Visitor Effectsupporting
confidence: 73%
“…Visitor presence has been recorded as influencing enclosure usage in other taxa [18], but any "visitor effect" needs to be measured and evaluated alongside other environmental influences occurring at the same time, e.g., weather conditions [19,20]. Visitor presence may reduce the amount of usable space in the captive environment and consequently reduce the animal's ability to perform a full behavioural repertoire [21]. Visitor presence can have a mixed effect on animals in zoos, ranging from potentially negative impacts [22], to neutral impacts or no effect [23] and positive influences on animal activity [24].…”
Section: Introductionmentioning
confidence: 99%
“…In one study of a group of captive gorillas in a zoo in the USA, the total absence of zoo visitors as a consequence of the pandemic lockdown produced no substantive effect on animal behavior [272]. Similar results were found in observations of the behavior of several species at zoos in Ireland and the United Kingdom [65]. An Australian aquarium, on the other hand, reported that its fish were "depressed" without their usual human visitors, and increased diver swim times in the larger tanks in an effort to improve their animals; welfare [273].…”
Section: Protecting the Welfare Of Animals In Zoos And Aquariumsmentioning
confidence: 57%
“…Horse owners in the United Kingdom expressed concern about their inabilities to ride or interact with their horses and the likely negative effects that such reduced interactions might have on those animals [64]. In yet another article, reduced interactions with zoo visitors as a consequence of mandated lockdowns was reported to increase vigilance and human avoidance in some zoo animal species, and increase human proximity-seeking in others [65]. Taken together, these data suggest that the current pandemic, in addition to its grave effects on the welfare of humans, may have significant impacts on nonhuman animal welfare.…”
Section: Potential Animal Welfare Impacts Of the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation